Augmented Virtualized Observation of Hidden Physical Quantities in Occupational Therapy - Fornaser, Alberto; De Cecco, Mariolino; Tomasin, Paolo; Zanetti, Matteo; Guandalini, Giovanni; Gasperini, Barbara; Ianes, Patrizia; Pilla, Francesco; Ghensi, Rossella (2018 International Conference on Cyberworlds (CW), 2018)
The human being is used to the management of those physical quantities that can be sensed by his/her five senses. The technology has grown following the constraint that tries to provide to the user senses interfaces that result natural and intuitive. With the born and the spread of virtual worlds, thanks to the Virtual and Augmented Reality revolution, such paradigm has enlarged comprising: (i) virtual parameters, (ii) directly sensed parameters, and (iii) indirectly sensed ones. The spread of sensing, connectivity, and intelligence in ubiquitous computing can occur using any device, in any location, and in any format and then fed back to the user has opened the problem/opportunity of how to synthesize the great amount of indirect and direct amount of data in a, still, natural way. This paper focuses on the development of an interface for data fruition by a physician or an occupational therapist in the context of the remote monitoring of disabled subjects that try different technological aids in a home scenario. The objective is the fruition of complex datasets in the most natural and intuitive way.